Manajemen Peserta Didik dalam Meningkatkan Prestasi Akademik dan Non Akademik Siswa SMPN 1 Lembah Sorik Marapi - Siti Asiyah; Novebri Novebri (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2024)
This research aims to explore student management in improving academic and non-academic achievements at SMPN 1 Lembah Sorik Marapi. Using a qualitative descriptive method with a case study approach, this research collects data through interviews, observation and documentation. The research results show that effective student management plays an important role in building student achievement. Factors such as careful planning, support for extracurricular activities, and student motivation directly impact academic and non-academic outcomes. However, obstacles were also found such as a lack of teacher professionalism in preparing Learning Implementation Plans (RPP) and variations in learning methods, which resulted in decreased student motivation. This research underlines the need for evaluation and improvement in the education system, especially to improve the balance between academic achievement and developing students' interests through non-academic activities.